Spinal Cord Cavernoma—Operative Strategy and Results in 30 Patients - Wachter, Dorothee; Psychogios, Marios; Gilsbach, Joachim Michael; Rohde, Veit (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background Many case reports and small series addressing the surgical management of spinal cord cavernoma have been published. However, only few larger series that would allow identifying operative strategies exist. After having treated 30 patients, we feel encouraged to report our experiences.Methods A total of 30 patients (13 men and 17 women) were mainly admitted to our institution because of sensory deficits (83.3%), paresis (33.3%), and bladder dysfunction (26.6%). Magnetic resonance imaging revealed a spinal cavernoma mostly in the thoracic region (63.3%). All patients underwent surgery. The relation between pial surface and cavernoma guided the choice of approach and the myelotomy site.Results After laminectomy/laminoplasty, median myelotomy was done in 16.7% to reach a medially located cavernoma. In 60.0%, myelotomy was located at the dorsal root entry zone, for which a (partial) hemilaminectomy was sufficient. The laterality of the location guided the bony approach in the remaining 23.3% with exophytic cavernoma. Immediately after surgery, neurological worsening was seen in 56.7%, an improvement in 10.0% and an unchanged neurological status in 33.3%. During the follow-up, the rate of neurological worsening dropped to 10.0%, the improvement rate increased to 50.0%. In 40.0% of the patients, the symptoms remained unchanged or returned to preoperative status.Conclusion The exact localization in relation to the pial surface guides the approach and area of myelotomy. In the majority of patients limited approaches are sufficient for successful cavernoma removal. In our series anterior approaches had not been necessary.
Keywords: spinal cord cavernoma; surgical techniques; approach